Fertilidade equina: a influência da idade materna - Souza, João Ricardo Malheiros de (2021)
The reduction in age-related fertility rates is reported in humans and horses. Although the characterization of the function is more evident to professionals during gynecological evaluations, especially after foaling, its interpretation in conjunction with the mare's age and embryonic quality must also be considered to favor the reproductive efficiency of the equine species. In this context, the first objective of this thesis was to investigate the influence of maternal age on the fertility of Thoroughbred mares during the postpartum period. The results obtained in this first study allowed us to identify that age influences the mare's postpartum fertility, with the age of ten being a cut-off point for reducing fertility. In addition, we identified that the interval between delivery and coverage can influence embryonic loss. It was also possible to identify that the fertility of the second estrus after delivery is higher when compared to the first estrus (foal heat). The second objective of this thesis was to investigate the effect of maternal age on the recovery and quality of embryos recovered from Mangalarga Marchador mares in embryo transfer programs. In addition, to verify the influence of progesterone supplementation in recipient mares after the transfer of embryos with different qualities. The results obtained in this second study allowed us to identify that the age of the donor mare influences the probability of recovery and the embryonic quality. It was also possible to identify that the embryonic quality and the group of recipients influenced the probability of pregnancy at 15 and 60 days after the transfer. While supplementation of progesterone in the recipients increased the probability of gestation at 15 and 60 days in embryos of different qualities. However, embryonic loss was dependent only on the recipient group. Taken together, the data show that maternal age influences the fertility of mares both in the postpartum period and in embryo transfer programs.